Histone Demethylase PHF8 Is Required for the Development of the Zebrafish Inner Ear and Posterior Lateral Line - He, Jing; Zheng, Zhiwei; Luo, Xianyang; Hong, Yongjun; Su, Wenling; Cai, Chengfu (Frontiers in Cell and Developmental Biology, 2020)
Histone demethylase PHF8 is crucial for multiple developmental processes, while awareness of its function in developing auditory organs needs to be increased. As insinuated by in situ hybridization (ISH) labeling, mRNA expression of PHF8 in the zebrafish lateral line system and otic vesicle was monitored. Knockdown of PHF8 by morpholino significantly disrupted the development of the posterior lateral line system, taking a toll on the capability for cell migration and decreasing the number of lateral line neuromasts. The knockdown of PHF8 also resulted in severe malformation of semicircular canal and otoliths in terms of size, quantity, and position during the development of the inner ear. Also, PHF8 functional loss induced a defective differentiation in sensory hair cells in both lateral line neuromasts and inner ear. ISH analysis of PHF8-lacking embryos showed alterations in the expression of many target genes of several signaling pathways in cell migration and deposition: Wnt and FGF pathways. In summary, the current findings established PHF8 as a novel epigenetic element in the development of auditory organs, thereby rendering it a potential candidate for hearing loss therapy.